An in-depth Study of the Concept of Chirality in Organic and Pharmaceutical Chemistry: Using Crystal Structure Data with 3D Visualization Software - Yang, Yi; Xu, Jian; Cao, Gao (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Chirality is an essential feature of life and a universal phenomenon in nature, chirality in chemistry and biochemistry is closely related to biological, spectroscopic and physical properties. The concept of chirality also has important applications in pharmaceutical chemistry. Objectives: This article aims to introduce how crystal structure data can be used in 3D visualization software to deepen students’ understanding of the concept of chirality in organic and pharmaceutical chemistry. Methods: Many crystal data examples are used to introduce chiral compounds and the absolute configuration of chiral factor, such as chiral atoms, axial chirality, planar chirality, spiral chirality and supramolecular chirality, the concrete teaching method is to import the crystal data into the visualization software, rotate it to the appropriate position, then labelled as the absolute configuration. The students were asked to do a set of chiral exercises based on crystal structure data. The effectiveness of this teaching method is judged by classroom test feedback. Results: We successfully established and applied a chiral teaching method based on crystal structure data. The test scores of students using this method were higher than those who had not used it before. Conclusion: This method can help students better understand the concept of chirality, improve the teaching quality and test scores and also lay a foundation for the application of chemistry database in teaching.
Keywords: Crystal structure data; Chirality; Pharmaceutical chemistry; Educational; informatization; Instructional tool; Reform in education